Odpowiedzi

  • Użytkownik Zadane
2010-01-04T20:04:24+01:00
A) 4a-2b-5a-a+6b+a-b = 4a - 5a + 6b - 3b = - a + 3b
b) 3x²y-4xy²+7xy²+x²y = 4x²y + 3 xy²
c) 0,3a+⅓ a²-a-0,4+a-0,2+½ = 0,3a + ⅔a² - 0,6 + 0,5 = 0,3a + ⅔a² -0,1
d)½ x-⅔ x²+¾-⅜ x-½+(dwie dziewiąte)x² = 11/8x - 4/9x² + ¼ =
= 1 3/8x - 4/9x² + ¼

/ <- ułamek
1 5 1
2010-01-04T20:11:29+01:00
A) 4a-2b-5a-a+6b+a-b= -a+3b
b) 3x²y-4xy²+7xy²+x²y= 4x²y+3xy²
c) 0,3a+⅓ a²-⅙ a-0,4+⅖ a-0,2+½= 16/30a +⅓ a²-0,1
d)½ x-⅔ x²+¾-⅜ x-½+(dwie dziewiąte)x²=⅛x-4/3x²+¼
2010-01-04T20:16:04+01:00
A) -a+3b
b)4x²y+ 3xy²
c)¹₃ a²+ ⁶₁₀ a -¹₁₀
d)-⁴₉x²+¹₈x+¹₄